O estudo do léxico na sala de aula: investigação do ensino dos processos semânticos de formação de palavras sob a perspectiva da Semântica de Contextos e Cenários (SCC) - Geraldo José Rodrigues Liska (2018)
This thesis had as main objective to elaborate a proposal of didactic-pedagogical approach appropriate for the Basic Education, from the observation realized in classroom of high school, from the perspective of the Semantics of Contexts and Scenarios (SCC). This proposal had the purpose of verifying how some semantic processes of lexical construction of the Portuguese are given, demonstrating how such processes can be more advantageously studied in the classroom, in a semantic, cognitive and lexical approach, related to the cultural aspects of the student's existence. In order to elaborate and present this proposal for a didactic-pedagogical approach, the methodology of this thesis was composed of a survey and documentary analysis on the teaching of lexicon in the Brazilian guiding documents that deal with the curricular organization and the matrices of national assessments for the Portuguese language, showing how the study of the lexicon and the teaching of words and meanings in specific Brazilian legislation, from the PCN (National Curricular Parameters for Education) to the final version of the BNCC (National Common Curricular Base), and how the lexicon approaches in the national assessments of Basic Education, from the Saeb tests (National System for the Evaluation of Basic Education) to the Enem (National High School Examination). We separated 27 questions from the Enem over nine years (2009-2017), with the skills matrix published in 2008. We then investigated how the Portuguese textbook collection (LDP) articulate with these documents in terms of word study, and investigated the knowledge of the students of a public school in the semantic processes of word formation, from a clipping of activities of the LDP collection adopted by the school and of discursive questions on the subject. In order to do this, we performed a clipping of activities from the LDP collection adopted by the school where this study was carried out, with which we prepared a notebook that was delivered to each student who participated in the research, in order to find out what they know about the lexicon and the semantic processes of word formation. By working with four dimensions in the teaching and learning process: legislation and guiding curriculum documents; national assessments; teaching materials; and the students' knowledge, the question that motivated this research could be answered: to what extent is the school neglecting the most important dimension of the study of lexicon and the relation between language and the speaker's existence in favor of formal secondary aspects of merely systemic order? Then, we have contextualized SCC, the theory adopted in this thesis, showing how it can be applied to teaching. Finally, the proposal of a didactic-pedagogical approach was presented, with activities in which metaphors and metonymy were analyzed through its structure (operation of crossing, displacing meanings), cognitive abilities (mental capacity to create analogies), culture (world view) and aesthetics (feeling of beauty). In addition to linguistic knowledge, with the application of educational techniques that promote socio-historical and cultural relations between the presented text and its production scenario, as well as between the text and the existential scenario of the student; cause and effect relationships between the activity itself and the formative objectives of the school; socio-historical and cultural applications between the pedagogical material and the student's out-of-school existence; and the possibility of the student identifying in the activity made a whole set of linguistic questions ranging from the very nature and function of the text and the specific questions of lexical construction to questions of a more ideologically evaluative order, , the use of humor for cathartic purposes in societies.